The Swedish version of the multidimensional inventory for religious/spiritual well-being – Part II: Development of a four-field typology - Podolin-Danner, Nikita; Wenzl, Magdalena; Knorr, Anna; Fuchshuber, Jürgen; Silani, Giorgia; Unterrainer, Human-Friedrich (Frontiers in Psychology, 2022)
Background: In the field of mental health, religiosity and spirituality have gained particular attention in recent decades. However, only a few studies to date have investigated the effects of different types of religiosity and spirituality. In association with the recent introduction of a Swedish version of the Multidimensional Inventory of Religious/Spiritual Well-Being (MI-RSWB-S), the present study aimed to identify possible types of Religious/Spiritual Well-Being by using cluster analyses and to examine the extracted groups for differences in the Sense of Coherence (SOC), the Big Five personality factors, and central aspects of religiosity. Additionally, the study design was intended to further contribute to the validation of the MI-RSWB-S. Methods: Based on a convenience sample of Swedish students (N = 1011), initially obtained for the development of the MI-RSWB-S, the study included the MI-RSWB-S, the 13-items Sense of Coherence Scale, the Ten Item Personality Inventory, and the Centrality of Religiosity Scale. For the statistical analysis, cluster analyses and one-way analyses of variance (ANOVAs) were conducted. Results: The cluster analyses yielded the following four groups: Religiosity and Spirituality High (n = 124), Religiously Oriented (n = 200), Spiritually Oriented (n = 149), and Religiosity and Spirituality Low (n = 538). The groups differed in most aspects of well-being, in the personality dimensions Agreeableness and Openness to Experience, as well as in central aspects of religiosity. In contrast, no differences were found for SOC, Extraversion, Conscientiousness, and Emotional Instability. Conclusion: Our results suggest that different types of Religious/Spiritual Well-Being are associated with mental health and personality dimensions in substantially different ways, thus offering an interesting potential for future research.